2002
DOI: 10.1046/j.1365-2826.2002.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Subsets of Serotonergic Neurones: Implications for Control of the Hypothalamic‐Pituitary‐Adrenal Axis

Abstract: Serotonergic systems play an important role in the regulation of behavioural, autonomic and endocrine responses to stressful stimuli. This includes modulation of both the hypothalamic-pituitary-adrenal (HPA) axis and the hypothalamic-spinal-adrenal (HSA) axis, which converge at the level of the adrenal cortex to regulate glucocorticoid secretion. Paradoxically, serotonin can either facilitate or inhibit HPA axis activity and stress-related physiological or behavioural responses. A detailed analysis of the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
236
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(261 citation statements)
references
References 150 publications
20
236
1
4
Order By: Relevance
“…18,64 In addition, collateral serotonergic projections arise from the DRN to target functionally related regions, such as those involved in stress response, anxiety and conditioned fear. 9,49 Introduction of rodents to stressful stimuli associated with increased anxiety and fear [65][66][67][68] or i.c.v. infusion of CRF, Ucn1 or Ucn2 14,22,48,69 is effective at increasing immediate-early gene expression within caudal regions of the DRN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,64 In addition, collateral serotonergic projections arise from the DRN to target functionally related regions, such as those involved in stress response, anxiety and conditioned fear. 9,49 Introduction of rodents to stressful stimuli associated with increased anxiety and fear [65][66][67][68] or i.c.v. infusion of CRF, Ucn1 or Ucn2 14,22,48,69 is effective at increasing immediate-early gene expression within caudal regions of the DRN.…”
Section: Discussionmentioning
confidence: 99%
“…9 Serotonin (5-HT) was found to regulate the hypothalamic-pituitary-adrenal (HPA) axis activity [9][10][11] and a variety of behavioral responses 12 during stressful challenges. Disturbed 5-HT functioning has a key role in the etiology of depression, as evidenced by altered expression of 5-HT receptors, decreased cerebrospinal fluid 5-hydroxyindoleacetic acid (5-HIAA) levels and the therapeutic efficacy of selective 5-HT reuptake inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…5-HT is clearly implicated in the modulation of motor activity (Jacobs and Fornal, 1997). The rostral-mid DRN projects to regions involved in motor control, such as the caudate putamen and substantia nigra (Imai et al, 1986;Lowry, 2002). Increases in central 5-HT during exercise coincide with the onset of fatigue (Blomstrand et al, 1988(Blomstrand et al, , 1989Davis and Bailey, 1997), and administration of a 5-HT2 receptor antagonist increases running time to exhaustion (Bailey et al, 1993), suggesting that decreasing 5-HT responses during exercise may delay fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…There is further topographical organization within the DRN itself. Although the possible significance of this organization will not be discussed here, Lowry and colleagues among others have shown that certain DRN subregions appear to be preferentially involved in stress and anxiety (Abrams et al, 2004(Abrams et al, , 2005Lowry, 2002;Maier and Watkins, 2005;Silva et al, 2002).…”
Section: Serotonin Releasementioning
confidence: 99%